Potensi Senyawa Turunan Terpenoid sebagai Agen Anti-Kanker - Amin, Saeful; Supriatna, Galuh Taruna; Ardian, Mohamad Idwar; Abdurrahman, Muhammad Iqmal (Penerbit Goodwood, 2025)
Purpose: This study aimed to analyze the potential of terpenoid derivatives as anti-cancer agents by reviewing various molecular mechanisms involved, findings from preclinical and clinical studies, and the challenges faced in their development. Methodology: A literature review approach was used, involving the collection, analysis, and synthesis of data from credible sources, to present a comprehensive understanding of the pharmacological properties and mechanisms of action of terpenoids. Critical evaluation of the selected studies was carried out to identify key findings and trends.. Results: This review shows that terpenoids have significant potential in cancer therapy through diverse molecular mechanisms, both as monotherapies and in combination with conventional treatments. Advances in drug delivery technologies, such as the use of nanoparticles and liposomes, have enhanced the stability and bioavailability of compounds, paving the way for more effective therapeutic applications. Conclusions: Terpenoid-based drug development shows strong promise in cancer treatment. Structural modifications have improved their efficacy and selectivity toward cancer cells, and innovative delivery systems have addressed challenges in bioavailability, supporting their role as safe and effective therapeutic alternatives. Limitations: This review was based on secondary data and lacked direct clinical validation. It does not provide detailed pharmacokinetic or pharmacodynamic profiles, and its potential interactions with standard chemotherapeutic agents remain underexplored. Contribution: This article synthesizes the molecular mechanisms and therapeutic potential of terpenoid derivatives as anticancer agents. This highlights the advances in delivery technologies and structural optimization, offering valuable insights for future drug development strategies.